2017
DOI: 10.21608/epsj.2017.7736
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Between Dietary Supplementation of Grape Pomace and Vitamin E as Antioxidant on Some Productive, Reproductive and Physiological Performance of Male and Female Aged Inshas Strain Chickens.

Abstract: This work was carried out to study the effect of dietary grape pomace and vit.E supplementation on some productive, reproductive and physiological performance traits of aged male and female Inshas strain chickens. A total number of 198 Inshas strain birds (180 laying hens and 18 cocks) 48-wks-old were used in this experiment up to 60 wks of age. All birds were individually weighed and randomly divided into 6 equal experimental groups (30 laying hens and 3 cocks of each) with three replicates (10 laying hens an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…These findings are similar to those of Francesch et al [ 21 ] who demonstrated that inclusion of 50 g/kg of grape seed in the diet of Penedes chicken did not significantly affect feed intake. These results further corroborate the results by Alm El-Dein et al [ 22 ] where dietary supplementation with up to 40 g/kg grape pomace did not affect feed intake in Inshas strain chickens. This suggests that the inclusion of RGP as a functional ingredient in chicken diets does not compromise the palatability of the diets.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are similar to those of Francesch et al [ 21 ] who demonstrated that inclusion of 50 g/kg of grape seed in the diet of Penedes chicken did not significantly affect feed intake. These results further corroborate the results by Alm El-Dein et al [ 22 ] where dietary supplementation with up to 40 g/kg grape pomace did not affect feed intake in Inshas strain chickens. This suggests that the inclusion of RGP as a functional ingredient in chicken diets does not compromise the palatability of the diets.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that the inclusion of RGP as a functional ingredient in chicken diets does not compromise the palatability of the diets. There were no significant dietary influences on overall BWG and FCR, which is consistent with the findings of Francesch et al [ 21 ] and Alm El-Dein et al [ 22 ] who reported no differences on growth performance of chickens fed grape pomace diets. Similarly, Lichovnikova et al [ 23 ] reported that the diet containing RGP did not have any significant effect on growth or FCR of broiler chickens.…”
Section: Discussionsupporting
confidence: 91%
“… ADF, acid detergent fiber; TDF, total dietary fiber; NDF, neutral detergent fiber; SDF, soluble dietary fibe; ADL, acid detergent lignin; ND, not detected. Supporting literature: 1 Alameldin [ 55 ]; Atalay [ 56 ]; Beres et al [ 57 ]; Chikwanha et al [ 28 ]; Ebrahimzadeh et al [ 58 ]; Ebrahimzadeh et al [ 59 ]; Erinle et al [ 45 ]; Goñi et al [ 18 ]; Gülcü et al [ 60 ]; Gungor et al [ 44 ]; Hosseini-Vashan et al [ 61 ]; Jonathan and Mnisi [ 62 ]; Leal et al [ 29 ]; Llobera and Cañellas [ 63 ]; Mirzaei-Aghsaghali et al [ 64 ]; Pérez Cid et al [ 32 ]; Valiente et al [ 65 ]; Vlaicu et al [ 66 ]; Winkler et al [ 67 ]; Yi et al [ 68 ]. 2 García-Rodríguez et al [ 69 ]; Goñ et al [ 70 ]; Karaman et al [ 71 ]; Milićević et al [ 26 ]; Pérez Cid et al [ 32 ]; Spanghero et al [ 72 ]; Tangolar et al [ 73 ]; Tangolar et al [ 74 ]; Yokotsuka and Singleton [ 75 ].…”
Section: Nutritional Properties Of Grape By-products and Strategies T...mentioning
confidence: 99%
“… SFA, saturated fatty acids; MUFA, monounsaturated fatty acids; PUFA, polyunsaturated fatty acids; GAE, gallic acid equivalents; TAE, tannic acid equivalents; CE, catechin equivalents; ND, not detected. Supporting literature: 1 Alameldin [ 55 ]; Beres et al [ 57 ]; Bustamante et al [ 27 ]; Ebrahimzadeh et al [ 59 ]; Erinle et al [ 45 ]; Goñi et al [ 18 ]; Gülcü et al [ 60 ]; Gungor et al [ 44 ]; Hosseini-Vashan et al [ 61 ]; Jonathan and Mnisi [ 62 ]; Kasapidou et al [ 76 ]; Leal et al [ 29 ]; Llobera and Cañellas [ 63 ]; Pérez Cid et al [ 32 ]; Vlaicu et al [ 66 ]; Yi et al [ 68 ]. 2 Goñi et al [ 70 ]; Gülcü et al [ 60 ]; Gungor et al [ 20 ]; Iuga and Mironeasa [ 15 ]; Karaman et al [ 71 ]; Milićević et al [ 26 ]; Pérez Cid et al [ 32 ]; Silva et al [ 77 ]; Tangolar et al [ 73 ]; Yokotsuka and Singleton [ 75 ].…”
Section: Nutritional Properties Of Grape By-products and Strategies T...mentioning
confidence: 99%
“…* Value is expressed as epicatechin equivalents; ** Only for skins of red grape pomace; *** Total flavonols. Supporting literature: 1 [ 15 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], 2 [ 15 , 33 ], 3 [ 15 , 19 , 34 , 35 , 36 ], 4 [ 35 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Figurementioning
confidence: 99%